(untitled) (Medical Forum Monthly, 2023)
Objective: To determine the impact of smartphone usage on sleep quality and to assess its deleterious effect in causing depression and anxiety among male adolescents. Study Design: Cross-sectional comparative study. Place and Duration of Study: This study was conducted at the Sleep Lab of Lahore General Hospital from April 2021 till September 2021. Materials and Methods: Thirty healthy male adolescents between age ranges of 18-24 years were divided into two groups depending upon the scores of Smartphone Addiction Scale: Group 1 (low smartphone users) and Group 2 (high smartphone users). Pittsburgh Sleep Quality Index was used for qualitative assessment of sleep among two groups. Beck Depression Inventory scores and Beck Anxiety Inventory scores reflected the psychological impacts of smartphone overuse on adolescents. The data collected was analyzed using SPSS version 22. Data was first checked for normality of distribution and then Independent T-test and its non-parametric alternate, Mann-Whitney U test were applied for comparison of sample means of two groups. A p-value of ≤ 0.05 was considered statistically significant. Results: Sleep quality was found to be significantly poorer in males with high smartphone usage as compared to the other group (p=0.041). Although Beck Depression Inventory (p=0.538) and Beck Anxiety Inventory (p=0.783) scores of high smartphone users were generally higher, but with no statistically significant difference among the two groups. Conclusion: Subjective sleep quality of high smartphone users was significantly impaired than the low smartphone users.